Teoria de obstrução e as classes de Stiefel-Whitney - Bezerra, Lenin Alexandre de Almeida (2020)
The main object of study in this work is the characteristic classes of vector bundles, precisely, we consider the Stiefel-Whitney classes. In general, we can interpret these classes as a way to determine the obstruction for the construction of linearly independent sections in a vector bundle. We present the axiomatic point of view and the de nition using the Obstruction Theory. We conclude by showing that the classes de ned using obstruction theory satisfy the requirements of the axiomatic de nition.